Análise do processo de Gestão da Informação e do Conhecimento no Orçamento Participativo do município de João Pessoa/PB - Saeger , Márcia Maria de Medeiros Travassos (2018)
This work presents the results of an immersive research in the context of participatory public management programs, with the general aim of analyzing the Information and Knowledge Management process in the Participatory Budgeting of the municipality of João Pessoa / PB (OPJP). The theoretical dimension was based on the conceptions derived from Information Science, constituted as it is as a field dedicated to studies on the information and knowledge phenomena, as well as to their contributions to the social and institutional development of the subjects, providing the appropriate theoretical framework for the studies on Information and Knowledge Management (GIC) in their different contexts of application. The working theoretical assumption is that GIC, as an integrated management process, constitutes the differential for the efficiency of public management, as it offers the necessary means and resources for information and knowledge to be used in benefit of public management and the improvement of the population’s life quality. As to the methodological dimension, the research is classified as exploratory and descriptive, with a qualitative approach, using as research strategies the bibliographic survey, the documentary research and the case study. The empirical field was composed of the OPJP’s Executive Secretariat, the regional assemblies and the municipal budget regions, considering the regional division adopted in the OPJP. The research included managers, articulators, municipal councilors, regional councilors of the OPJP and members of the communities in each region of the city. For data collection, it made instrumental use of semi-structured interview, focus groups, participant observation and documentary analysis. The results obtained from the data collection were treated through content analysis, with categories and subcategories constructed from the GIC process adopted in this work. The results of this research revealed that there are currently IG and GC actions adopted by OPJP management; however, such actions do not originate from a GIC process specifically planned for the Program. Thus, the management of the information flows existing in the OPJP is not conducted in a professional way, presenting limitations on its results, which end up compromising the wide access and use of information by the different actors related to the Program. The results also allowed to identify the absence of a social protagonism committed to citizenship in the community members, who participate in the Program in a limited way. Such findings evidenced the need for the elaboration of guidelines capable of contributing to the implementation of a GIC process for the OPJP. In this sense, first it was identified the need for the OPJP management to establish actions of educational nature for the people of João Pessoa, fostering a citizen and participatory awareness, educating these subjects for citizenship, besides stimulating the development of informational skills so that the access, the production and the dissemination of information and knowledge allow the necessary dialogue between these subjects in a critical and reflective manner. Besides, technical guidelines have been proposed, composed of a set of actions that will enable the implementation of GIC in the Program’s management. It is concluded that the adoption of such guidelines may contribute to a more active participation of citizens, meeting the foundations of the OPJP and providing the improvement of the management of the information flows of the Program.